Pengaruh Kualitas Layanan Terhadap Kepuasan Peserta Didik Di Sdn Kecamatan Batuan Kabupaten Sumenep - Nuzuliati, Nurdian; Pramo, Sapto (Soetomo Magister Ilmu Administrasi, 2023)
Purpose – The purpose of this study is to determine the service that is reliable, responsive, convincing, empathetic and facility providers affect the satisfaction of students at SDN Kecamatan Batuan. Design/Methodology/Approach - This type of research in the thesis is a type of exploratory discriptive research. Because in this study want to know the relative events. Distribution and influence between variables, by taking samples from a population and using questionnaires as the main data collection. The sample used in this study was 88 students with details of class V sample as many as 47 students and class VI sample as many as 41 students. Findings - Reliable and responsive services do not have a significant effect on student satisfaction, while reassuring, empathetic and facility services have a significant effect on student satisfaction. Social Implications/Values - Institutions can create a more comfortable atmosphere and enhance kinship/image creation, be more flexible and more emotionally expressive in behavior. To achieve the income target, it is necessary to increase discipline so that students can be motivated to carry out the main tasks and functions and be more enthusiastic in carrying out the teaching and learning process.Keywords: Satisfaction, Reliable Service, Responsive Service, Reassuring Service, Empathetic Service, Facility Provider Service, Public Elementary School.